KAJIAN EIKSPERIMENTAL FAKTOR REDAMAN BETON POLIMER DENGAN MODAL TESTING - Isneini Semendawai, M.
Polimer concrete has different behaviour and different mechanic characteristic than others because it depends on material polimer so that it caused to do research to study of its behaviour and mechanic caracteristic. This polimer concrete was made with prepacked system, consists of unsaturated polyester (UP) added with styrene monomer (SM) as binder matrix, UP and SM setting caused by adding cobalt napthenate solution (CoNp) as a prornotor and methyl ethyl ketone peroxide (MEKPO) as an initiator, and also coarse aggregate as inclusion. In this composition did variation of percentage of polimer and fly ash as a filler, beside that the other materials were constant. The object of this research is to find out mechanic characteristic and influence of percentage of polimer or filler toward value of damping (loss factor), to find out influence of polymer, series of laboratory tests were carried out. From analysis of tests result, compressive strength reached 19,02 41,489 MPa, beside its maximum strength was reached at 55% content of polymer, also obtained from splitting test 4,300 6,023 MPa and maximum of tensile strength was reached at 65% content of polymer. Values of modulus 952,4 1956,4 MPa and modulus of elastisity that were gotten from flexural strength 1212,985 3812,067 MPa, 0,12 0,21 Poison's ratio, values of modulus increased from 50% then 35% up to 45% content of filler, beside that values of damping (loss factor) 1,669 3, 017%. Result also showed that more and more a lot content of polymer caused loss factor (r) damping coeffisien (c) and damping ratio (?) becames decrease, it also showed that fly ash influenced to increase dynamic parameter.